Physicochemical and hygienic-sanitary quality of honey marketed in Chókwè city (Research, Society and Development, 2023)
The present study aimed to evaluate the hygienic-sanitary conditions and the physical-chemical parameters of honey bees with emphasis on understanding the risks to health. The experiment was conducted in a completely randomized design with 5 samples, 3 from artisanal production (A, B and C) and 2 from industrial production (Youngs honey (D) and Goldcrest (E)). Analyzes such as titratable acidity by titration with 0.1N sodium hydroxide solution (NaOH), soluble solids content, refractometry, pH, potentiometry, humidity, gravimetry and ash by incineration were carried out for the physical-chemical characterization. The hygienic-sanitary characterization was performed for molds and yeasts using the Spread Plate method. Data were evaluated using the statistical software RStudio 4.2.1 at 5% significance of the Tukey test. The pH was fixed in the range of 3.28 to 4.30, soluble solids from 76.36 to 77.10 ºBrix, titratable acidity at the level of 4.14 to 6.10 meq/mL, moisture content of 12.07 to 17.12% and ash from 0.29 to 4.34%. The microbiological characterization showed the presence of molds in the range of 1.5x10 to 4.9x10. On the other hand, an uncountable load was verified in the yeast count in samples A and B, exceeding the limit established by the Technical Regulation of Quality and Identity of Honey. In terms of physical-chemical properties, no significant differences were found between artisanal and industrialized honey. The level of mold in all samples met recommended standards for honey and there was evidence of compliance with good manufacturing and hygienic-sanitary practices.